Effects of different types of contingent tactile stimulation on crying, smiling, and sleep in newborns: An observational study. Issue 5 (1st June 2012) - Cecchini, Marco; Baroni, Eleonora; Di Vito, Cinzia; Piccolo, Federica; Aceto, Paola; Lai, Carlo
Abstract Sleep, the brain and the ability to interact with the environment change a great deal over the first year of life; however, there are no studies on the possible influence of different environmental stimulations on the organization of subsequent sleep–wake cycles in infants. The hypothesis of this study was that greater continuity of contingent tactile stimulation decreases crying behavior, subsequent active sleep (AS) and its fragmentation, and increases smiling behavior and subsequent quiet sleep in newborns. Forty out of the 82 newborns (15‐ to 30‐hr old) of the initial sample satisfied the inclusion criteria and completed the first cycle of sleep during the period between two feedings. The 40 newborns were randomly assigned to four groups after 2′ of baseline observation: continuous stimulation (CS, n = 10); discontinuous nonperiodic stimulation (DnPS, n = 10); discontinuous periodic stimulation (DPS, n = 10); absent stimulation (AbS, n = 10). During baseline measurements, there were no significant differences in crying and smiling behaviors between the four groups, while during the subsequent stimulated wake, the CS group compared to the DnPS group showed more smiling (p < .05) and less crying (p < .05), longer poststimulation wake before sleep (p < .01) as well as AS with a lower percentage of grouped‐rapid eye movements [grouped REM (GREM); p < .001]. The number of GREM during AS was negatively correlated to the number of smiles (p < .05) and positively to the number of cries (p < .05) of the previous stimulated wake. These findings suggest that, after birth, different continuity levels of contingent tactile stimulations may affect crying and smiling behaviors and the organization of behavioral states. AS could have an important role in processing affective states. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 508–517, 2013